Closed-Loop Supply Chains for Cradle to Cradle Products - Katharina Kalogerakis; Viktoria Drabe; Mugundan Paramasivam; Cornelius Herstatt (Sustainability in Logistics and Supply Chain Management: New Designs and Strategies. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 21, 2015)
As attention around environmental sustainability themes is increasing, a multiple attribute environmental sustainability philosophy called Cradle to Cradle (C2C) has recently been developed and presented. The C2C concept provides a new vision of environmental sustainability to companies, to do "more good" to the environment rather than "less bad". An important and central aspect is to eliminate the concept of waste by closing technical as well as biological cycles. The aim of this paper is to analyze which factors from closed-loop supply chain management can facilitate the realization of the technical cycle of C2C certified products. Based on six case studies of different companies, we investigate which factors of existing closed-loop supply chain concepts are critical for the C2C technical cycle. Altogether this research links the theory of closed-loop supply chains to the concept of C2C and provides new insights concerning successful implementation of the technical cycle.
10419/209190; https://econpapers.repec.org/RePEc:zbw:hiclpr:21
Keywords: 650; Cradle to Cradle; Product Recovery; Closed-loop Supply Chain; Sustainability